Options for treatment correction in children with atopic dermatitis - Aleksandra I. Kafarova; Victoria A. Smirnova; Tatyana V. Sokolova; Irina L. Solovyeva (Union of pediatricians of Russia, 2023)
Background. Atopic dermatitis (AD) treatment is based on clinical recommendations (CR, 2021). It is reasonable to use other effective treatment methods due to continuous and often relapsing course of dermatosis, and thus physiotherapy treatment is important.Objective. The aim of the study is to evaluate the efficacy of chromotherapy with a spectrum of 470 nm (blue spectrum) in children with AD complicated by secondary infection.Methods. The study included 40 children aged from 2 to 12 years. All patients received standard treatment regimen according to the current CR and were divided into 2 groups, equal in number (20 patients each): the control group (CG - only traditional therapy), and the experimental group (EG - traditional therapy + blue spectrum chromotherapy (470 nm)).Results. The SCORAD index (the sum of objective and subjective features) before treatment in the whole patient cohort was 32.5 ± 6.99 points, which corresponds to the moderate-severe form of the disease. The positive effect of therapy was registered in all patients (n = 40). Persistent process stabilization on the 7th day 7 of treatment in EG was observed in 8 patients, and in CG - in 2 (40% and 10%, respectively); p = 0.065. After the end of the treatment (10th day) persistent remission prevailed in EG and was registered in 90% (n = 18) of patients, and in CG - only in half of all patients, 55% (n = 11); p = 0.031. The evaluation of the AD severity due to the SCORAD index in patients with residual clinical manifestations clearly indicates that in EG its value corresponded to a mild disease course (p < 0.001), and in CG - the lower border of the moderate-severe and the upper border of the mild disease course (p < 0.05).Conclusion. The use of blue spectrum chromotherapy in treatment of children with AD is the effective and accessible method that can be used as an addition to traditional treatment in cases with secondary infectious complications. Its use has a potential to exclude polypragmasy in this dermatosis treatment.